(untitled) (Journal of Engineering, 2024)
This research aimed to assess the effect of immersing heat-cured acrylic resin in tea tree oil solution as a long-term disinfectant. The effect of immersing heat-cured acrylic resin in tea tree oil denture cleanser 180 times on its hardness, UV absorption, water sorption, and solubility was investigated in this study. Ninety heat-cured acrylic resin specimens were prepared and divided into three sets, each consisting of 30 specimens. The specimens were placed in different solutions: distilled water, a solution containing 0.75% tea tree oil, and a solution containing 1% tea tree oil. Each group comprised 10 specimens, and each specimen was submerged for 10 min in accordance with its group. This process was repeated 180 times. After 180 times of immersion, tea tree oil solutions showed non-significant differences (P > 0.05) in surface hardness and statistically significant changes in UV absorption, water sorption, and solubility (P < 0.05). The heat-cured acrylic resin immersed 180 times showed that 0.75% tea tree oil concentration improved solubility and water absorption but not surface hardness and UV absorption. Moreover, 1% tea tree oil concentration enhanced water sorption and solubility. It also decreased UV absorption, but it did not influence hardness. Thus, a 0.75% tea tree oil disinfectant solution is intended to be a long-term denture cleanser.